Contemporary risks and opportunities: re-localizing Malayness in popular TV fiction - Mohd Muzhafar Idrus (Taylor’s University, Subang Jaya, 2016)
The escalation of Malay television fiction (TV fiction, hereafter) series in recent years can be partly explained by TV producers tailoring their products to match the patterns of audience’s pleasure. Themes of love dominate the plots, and almost always the good is pitted against evil, rich against poor, where ultimately the good always wins. The formula may be clichéd, but in a world where news of war, terrorism, diseases, and conflicts often make the headlines, respite from harsh realities of life can often be found in TV fiction. This paper focuses on three TV series, Julia, On Dhia, and Adam & Hawa which draw over 11 million viewers in 2013 to study how these series highlight the return to the imaginary ‘good old days’ that reiterates Malay cultural identities. Specifically, despite their constant engagement with Western imposed modernization, the TV fiction set against the backdrop of globalization can encourage TV viewers to regress, re-routing their ways to rediscover their ‘local’ that is often dismissed, neglected, or forgotten. Premised on this postcolonial perspective, selected TV fiction’s narrative exchanges are analyzed using conversation analysis (Hutchby & Wooffitt, 2008). Drawing from theory of cultural hybridity, it is highlighted that these series show reversion to Malay adat (customs) in Julia, On Dhia, and Adam & Hawa, useful for understanding of the (re)making of Malayness. This regress to Malay adat through precepts of forgiveness and repentance governs the Malay Muslim worldviews; although the TV fiction set in modern settings can potentially disrupt and risk local sensitivities and norms, re-localization of Malayness holds that Malay subjects will remain allegiant to the receptacle of recognizable, local Malay tradition.